Validation of Game-Based Activities in Teaching Grade 7-Biology - Lasala Jr, N. L. (Jurnal Pendidikan IPA Indonesia, 2022)
The use of game-based activities in education has been recognized as an innovative alternative instructional material. As any sort of instructional material is essential to the teaching and learning process, it is imperative to check its quality before widespread utilization to ensure effectiveness. This study aims to evaluate the validity of the developed lessons in Ecosystem integrating game-based activities (GBAs) namely (1) THE CONQUEST, (2) ECO-DAMA, (3) ECO-CHALLENGE, and (4) ECO-WARRIOR for Grade 7 Biology. This research employed descriptive developmental research design involving 8 experts and 66 students chosen through purposive sampling. Experts used the DepEd standards for non-print resources while students were given the evaluation checklist and asked to write journals for the validation. Results show that the GBAs met all of the LRMDS DepEd's standards for non-print resources and were deemed "very satisfactory" by both the students and the experts implying high validity. Additionally, the students' pre-test and post-test results revealed that integrating GBAs improved their academic performance. The experts and students acknowledged the potential for GBAs to make classes engaging, instructive, and fun, supporting the validity of the developed GBAs. This study concludes that the use of GBAs is a valid and effective approach in Science education and the developed GBAs can be used as supplemental and cutting-edge instructional materials for teaching Ecosystem. This study adds to the body of knowledge exploring the potentials of GBAs for educational purposes and promotes the use of GBAs in similar fields of study.